Depression symptoms and cognitive function among individuals with advanced HIV infection initiating HAART in Uganda - Ronald Allan; Robertson Kevin; Allebeck Peter; Musisi Seggane; L Skolasky Richard; Nakasujja Noeline; Katabira Elly; Clifford David B; Sacktor Ned (BMC Psychiatry, 2010)
Abstract Background Among patients with HIV infection, depression is the most frequently observed psychiatric disorder. The presence of depressive symptoms and cognitive dysfunction among HIV patients has not been well studied in Sub-Saharan Africa. Initiation of highly active antiretroviral therapy (HAART) may have an effect on the prevalence and the change over time of depression symptoms and cognitive impairment among HIV-positive individuals. Methods We recruited 102 HIV-positive individuals at risk of cognitive impairment who were initiating HAART and 25 HIV-negative individuals matched for age and education. Depression was assessed using the Centre for Epidemiologic Studies Depression Scale (CES-D). Neurocognitive assessment included the International HIV Dementia Scale (IHDS), an 8 test neuropsychological battery and the Memorial Sloan Kettering scale. Assessments were carried out at 0, 3 and 6 months. Results The HIV-positive group had more respondents with CES-D score > 16 than the HIV-negative group at all 3 clinic visits (54%Vs 28%; 36% Vs 13%; and 30% Vs 24% respectively; all p < 0.050 OR 2.86, 95% CI: 1.03, 7.95, p = 0.044). The HIV positive group had higher likelihood for cognitive impairment (OR 8.88, 95% CI 2.64, 29.89, p < 0.001). A significant decrease in the mean scores on the CES-D (p = 0.002) and IHDS (p = 0.001) occurred more in the HIV-positive group when compared to the HIV-negative group. There was no association between clinical Memorial Sloan Kettering score and depression symptoms (p = 0.310) at baseline. Conclusion Depression symptomatology is distinct and common among cognitively impaired HIV patients. Therefore individuals in HIV care should be screened and treated for depression.